2009
DOI: 10.1016/j.molimm.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Defective B cell ontogeny and humoral immune response in mice prematurely expressing human complement receptor 2 (CR2, CD21) is similar to that seen in aging wild type mice

Abstract: Mice prematurely expressing human CR2 (hCR2) in the B cell lineage have a defective B cell ontogeny and humoral immune response. We have previously determined altered tyrosine phosphorylation patterns within hCR2 transgenic mice, suggesting that irreversible changes in B cell signaling pathways had occurred, which could explain the B cell unresponsiveness associated with hCR2 transgene expression. In support of that assertion, we found that increasing antigen dose or addition of adjuvant had a minimal impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Our data in the hCR1 mice does not demonstrate loss B cells in the bone marrow compartment (supplemental figure 2b), even with homozygous hCR1 expression, and indicate that either expression level or the ligand interactions are critical in this setting. It is also clear from our analysis of hCR2 hi mice that the signaling events during this phase of B cell development overrides or renders subsequent signals through murine CR1/2 irrelevant and thus, represents a dominant negative phenotype with respect to normal signaling via mCR1/2 (Birrell et al, 2005; Kulik et al, 2007; Pappworth et al, 2009; Twohig et al, 2007; Twohig et al, 2009). Our analysis of the hCR1 mice would suggest that this situation is not the case in the hCR1 mice as mice expressing both hCR1 and endogenous mCR1/2 have a marginally better immune response and suggests some co-operation between the function of hCR1 and mCR1/2.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our data in the hCR1 mice does not demonstrate loss B cells in the bone marrow compartment (supplemental figure 2b), even with homozygous hCR1 expression, and indicate that either expression level or the ligand interactions are critical in this setting. It is also clear from our analysis of hCR2 hi mice that the signaling events during this phase of B cell development overrides or renders subsequent signals through murine CR1/2 irrelevant and thus, represents a dominant negative phenotype with respect to normal signaling via mCR1/2 (Birrell et al, 2005; Kulik et al, 2007; Pappworth et al, 2009; Twohig et al, 2007; Twohig et al, 2009). Our analysis of the hCR1 mice would suggest that this situation is not the case in the hCR1 mice as mice expressing both hCR1 and endogenous mCR1/2 have a marginally better immune response and suggests some co-operation between the function of hCR1 and mCR1/2.…”
Section: Discussionmentioning
confidence: 96%
“…The hCR2 hi mice displayed marked reduction in peripheral blood B cell numbers, a reduction in IgG isotype antibodies, loss of follicular and reciprocal expansion of ‘innate’ B cell populations in the spleen and as well as a marked reduction in the immune response to both T dependent and T independent antigens beyond that seen in CR1/2 deficient mice. Indeed, the hCR2 hi mice were subsequently shown to be highly resistant to collagen induced arthritis and have a degree of protection from developing systemic autoimmune disease as a result of these changes (Kulik et al, 2007; Pappworth et al, 2009; Twohig et al, 2007; Twohig et al, 2009). All these alterations in B cell function are almost certainly a result of the premature expression of CR2 on the B cell surface during B cell development in the bone marrow (Kulik et al, 2007), which irreversibly alter the signaling potential of these B cells whether in the presence or absence of endogenous mCR1/2 expression or signaling (Birrell et al, 2005; Kulik et al, 2007; Marchbank et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Breg reciprocally promote development of FoxP3 + regulatory T cells (Treg) and exert similar immune-suppressing activities [101,102]. The first indication of a change in these cell types during aging was shown by Twohig et al (2009). They reported an increased percentage of Breg in mice and suggested that the expansion suppresses the increasing numbers of autoreactive B cells.…”
Section: Lymphocytesmentioning
confidence: 99%
“…They reported an increased percentage of Breg in mice and suggested that the expansion suppresses the increasing numbers of autoreactive B cells. The increased percentages of Breg, together with the decrease in function of dendritic cells (DC), may cause a decline in effector CD4 + T cell function [103].…”
Section: Lymphocytesmentioning
confidence: 99%